How to cheat at IIS 7 server administration. - Adams, Chris ("How to cheat--", 2007)
According to Microsoft, Internet Information Services (IIS) 7.0 is a web server that provides a secure, easy to manage platform for developing and reliably hosting Web applications and services. With the new version of IIS, there are more security options, 40 new feature models that allow administrators to customize their settings, and a new set of administration tools. Administrators migrating from version 6 will find this How to Cheat book the perfect vehicle for getting up to speed fast on the new version. IIS version 7 is the perfect product for the How to Cheat series. This new version from Microsoft is an ambitious overhaul that tries to balance the growing needs for performance, cost effectiveness, and security. For the average SysAdmin, it will present a difficult migration path from earlier versions and a vexing number of new features. How to Cheat promises help get IIS 7 up and running as quickly and safely as possible. *Provides the multi-tasked SysAdmin with the essential information needed to perform the daily tasks *Emphasizes best-practice security measures *Cover the major new release of IIS 7, which will create significant challenges for IT managers.